2018
DOI: 10.3892/etm.2018.5832
|View full text |Cite
|
Sign up to set email alerts
|

3-Methyladenine and dexmedetomidine reverse lipopolysaccharide-induced acute lung injury through the inhibition of inflammation and autophagy

Abstract: Abstract. The aim of the present study was to investigate the effects of 3-methyladenine (3-MA) and dexmedetomidine (DEX) pretreatment on lipopolysaccharide (LPS)-induced acute lung injury (ALI) and the potential mechanism underlying the effects. LPS was instilled into the trachea of BALB/c mice to induce the ALI model. Solutions of 3-MA or DEX were intravenously injected into the mice 1 h later to establish the 3-MA and DEX groups. On days 1, 3 and 5 after the injections, arterial blood gas analysis was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…22 Previous animal model studies have reported that DEX has a lung-protective effect involving IL-6 inhibition and endothelin-induced inflammatory reaction. [23][24][25] We observed that DEX decreases the plasma and lung tissue levels of IL-6 and TNF-α during the perioperative period. DEX partially attenuates lung injury by activating PI3K/Akt/HIF-1α signaling pathway and significantly reduces serum inflammatory cytokine levels in rat models of obstructive jaundice.…”
Section: Discussionmentioning
confidence: 83%
“…22 Previous animal model studies have reported that DEX has a lung-protective effect involving IL-6 inhibition and endothelin-induced inflammatory reaction. [23][24][25] We observed that DEX decreases the plasma and lung tissue levels of IL-6 and TNF-α during the perioperative period. DEX partially attenuates lung injury by activating PI3K/Akt/HIF-1α signaling pathway and significantly reduces serum inflammatory cytokine levels in rat models of obstructive jaundice.…”
Section: Discussionmentioning
confidence: 83%
“…The present data indicated that oxaliplatin injection could increase the levels of LPS in the serum and DRG of mice, which was decreased following treatment with hydrogen-rich water; however, these differences were not reflected in the spinal cords. Since TLR4 is a ligand of LPS, 33 TLR4 was further examined, and the result was the same as that for LPS ( Figure 7 ). It can therefore be inferred that hydrogen-rich water affects the gut microbiota and reduces the occurrence of oxaliplatin-induced CINP through the LPS-TLR4 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, with the application of autophagy inhibitors, the expression of inflammatory genes is enhanced in adipocytes; conversely, activation of autophagy reduces the expression of inflammatory genes, indicating that autophagy can balance the inflammatory response [21]. In contrast, with the autophagy inhibitors, 3-methyladenine blocked autophagy activity and reversed LPS-induced acute lung injury through the inhibition of inflammation and autophagy [22]. These observations indicated that the protective or detrimental effect of autophagy activation depends on cell types, stimuli, and environment, and the directionality of the effect may be context dependent.…”
Section: Introductionmentioning
confidence: 99%